Investigation of the RFC1 Repeat Expansion in a Canadian and a Brazilian Ataxia Cohort: Identification of Novel Conformations - Akçimen, Fulya; Ross, Jay P.; Bourassa, Cynthia V.; Liao, Calwing; Rochefort, Daniel; Gama, Maria Thereza Drumond; Dicaire, Marie-Josée; Barsottini, Orlando G.; Brais, Bernard; Pedroso, José Luiz; Dion, Patrick A.; Rouleau, Guy A. (Frontiers in Genetics, 2019)
A biallelic pentanucleotide expansion in the RFC1 gene has been reported to be a common cause of late-onset ataxia. In the general population, four different repeat conformations are observed: wild type sequence AAAAG (11 repeats) and longer expansions of either AAAAG, AAAGG or AAGGG sequences. However only the biallelic AAGGG expansions were reported to cause late-onset ataxia. In this study, we aimed to assess the prevalence and nature of RFC1 repeat expansions in three cohorts of adult-onset ataxia cases: Brazilian (n=23) and Canadian (n=26) cases that are negative for the presence of variants in other known ataxia-associated genes, as well as a cohort of randomly selected Canadian cases (n = 128) without regard to a genetic diagnosis. We identified the biallelic AAGGG expansion in only one Brazilian family which presented two affected siblings, and in one Canadian case. We also observed two new repeat conformations, AAGAG and AGAGG, which suggests the pentanucleotide expansion sequence has a dynamic nature. To assess the frequency of these new repeat conformations in the general population, we screened 163 healthy individuals and observed the AAGAG expansion to be more frequent in cases than in control individuals. While additional studies will be necessary to asses the pathogenic impact of biallelic genotypes that include the novel expanded conformations, their occurrence should nonetheless be examined in future studies.